Brain lesion scores obtained using a simple semi-quantitative scale from MR imaging are associated with motor function, communication and cognition in dyskinetic cerebral palsy - Laporta-Hoyos, O.; Fiori, S.; Pannek, K.; Ballester-Plané, J.; Leiva, D.; Reid, L.; Pagnozzi, A.; Vázquez, Élida; Delgado, I.; Macaya, A.; Pueyo, R.; Boyd, Roslyn (Elsevier BV, 2018)
To characterise brain lesions in dyskinetic cerebral palsy (DCP) using the semi-quantitative scale for structural MRI (sqMRI) and to investigate their relationship with motor, communication and cognitive function. Materials and methods: Thirty-nine participants (19 females, median age 21y) with DCP were assessed in terms of motor function, communication and a variety of cognitive domains. Whole-head magnetic resonance imaging (MRI) was performed including T1-MPRAGE, T2 turbo spin echo (axial plane), and fluid attenuated inversion recovery images (FLAIR). A child neurologist visually assessed images for brain lesions and scored these using the sqMRI. Ordinal, Poisson and binomial negative regression models identified which brain lesions accounted for clinical outcomes. Results: Brain lesions were most frequently located in the ventral posterior lateral thalamus and the frontal lobe. Gross (B = 0.180, p <.001; B = 0.658, p <.001) and fine (B = 0.136, p =.003; B = 0.540, p <.001) motor function were associated with global sqMRI score and parietal involvement. Communication functioning was associated with putamen involvement (B = 0.747, p <.028). Intellectual functioning was associated with global sqMRI score and posterior thalamus involvement (B = -0.018, p <.001; B = -0.192, p <.001). Selective attention was associated with global sqMRI score (B = -0.035, p <.001), parietal (B = -0.063, p =.023), and corpus callosum involvement (B = -0.448, p <.001). Visuospatial and visuoperceptive abilities were associated with global sqMRI score (B = -0.078, p =.007) and medial dorsal thalamus involvement (B = -0.139, p <.012), respectively. Conclusions: Key clinical outcomes in DCP are associated with specific observable brain lesions as indexed by a simple lesion scoring system that relies only on standard clinical MRI.